2014
DOI: 10.1142/s2339547814500083
|View full text |Cite
|
Sign up to set email alerts
|

A novel ultrathin collagen nanolayer assembly for 3-D microtissue engineering: Layer-by-layer collagen deposition for long-term stable microfluidic hepatocyte culture

Abstract: The creation of stable hepatocyte cultures using cell-matrix interactions has proven difficult in microdevices due to dimensional constraints limiting the utility of classic tissue culture techniques that involve the use of hydrogels such as the collagen “double gel” or “overlay”. To translate the collagen overlay technique into microdevices, we modified collagen using succinylation and methylation reactions to create polyanionic and polycationic collagen solutions, and deposited them layer-by-layer to create … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 53 publications
1
32
0
Order By: Relevance
“…The hepatocytes lose their functions and phenotype when they are isolated from the natural niche (8,9). Many in vitro models have been introduced to improve the hepatocyte activities and morphology (43).…”
Section: Glycosaminoglycans Have Been Shown To Increasementioning
confidence: 99%
“…The hepatocytes lose their functions and phenotype when they are isolated from the natural niche (8,9). Many in vitro models have been introduced to improve the hepatocyte activities and morphology (43).…”
Section: Glycosaminoglycans Have Been Shown To Increasementioning
confidence: 99%
“…While many potential polymers could be utilized for good results in terms of hepatocyte morphology, function, co-culture with LSECs, and CYP 1A1/2 activity have been reported for up to 12 days using chitosan and hyaluronic acid 85,207 . We have recently been able to translate this approach to a microfluidic device for hepatocyte culture using charge modified collagen strands creating a ECM barrier that is on the order of ~100 nm and have also shown long-term stability of important hepatic functions 208 .…”
Section: In-vitro Platforms For Mimicking the Liver Physiology Andmentioning
confidence: 99%
“…We have also developed a new ultrathin collagen coating 208 solution for microfluidic applications which circumvents problems that arise when translating hydrogel methodology to the microfluidic realm. We will use this technique to further reduce dimensions in our device and approach more realistic scenarios for interaction between different cell types.…”
Section: A Critique Of the History And Going Forward: Challenges Amentioning
confidence: 99%
“…McCarty et al also reported that albumin secretion by cultured hepatocytes increases steadily if an ultrathin, pure collagen nanolayer is deposited on top of the cells, reaching a plateau on day 10 of culture; without this top matrix, albumin secretion by hepatocytes apparently remains low [23]. Moreover, the actin filaments in seeded hepatocytes are diffuse or radially oriented around the nucleus in the absence of a top matrix layer; however, actin fibers are reorganized along the cell-to-cell borders in hepatocytes covered with the ultrathin collagen layer [23].…”
Section: Effcts Of No In the Presence Of Shear Stress On Ammonia Decomentioning
confidence: 98%
“…Moreover, the actin filaments in seeded hepatocytes are diffuse or radially oriented around the nucleus in the absence of a top matrix layer; however, actin fibers are reorganized along the cell-to-cell borders in hepatocytes covered with the ultrathin collagen layer [23].…”
Section: Effcts Of No In the Presence Of Shear Stress On Ammonia Decomentioning
confidence: 99%